2020
DOI: 10.1101/2020.12.15.20248214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics and Risk Factors for Hospitalization and Mortality among Persons with COVID-19 in Atlanta Metropolitan Area

Abstract: Background: We present data on risk factors for severe outcomes among patients with coronavirus disease 2019 (COVID-19) in the southeast United States (U.S.). Objective: To determine risk factors associated with hospitalization, intensive care unit (ICU) admission, and mortality among patients with confirmed COVID-19. Design: A retrospective cohort study. Setting: Fulton County in Atlanta Metropolitan Area, Georgia, U.S. Patients: Community-based individuals of all ages that tested positive for SARS-CoV-2. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 15 publications
3
16
0
2
Order By: Relevance
“…However, the precise estimate of the role of neurological diseases, and the comparison between neurological vs. non-neurological patients, are mainly limited by the fact that patients with neurological diseases are frequently older and more affected by other comorbidities. A retrospective analysis of 2820 patients reported increased adjusted odds of having severe COVID-19 and fatal outcome in patients with neurological disease [16]. Two observational studies reported a 4.6-fold [17] and a 2.9-fold [18] higher COVID-19-related mortality in neurological patients, evaluated by a multivariate approach, while other studies reported, in univariate analyses only, a significant association between mortality and neurological diseases [23] or cerebrovascular and neurodegenerative disorders [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the precise estimate of the role of neurological diseases, and the comparison between neurological vs. non-neurological patients, are mainly limited by the fact that patients with neurological diseases are frequently older and more affected by other comorbidities. A retrospective analysis of 2820 patients reported increased adjusted odds of having severe COVID-19 and fatal outcome in patients with neurological disease [16]. Two observational studies reported a 4.6-fold [17] and a 2.9-fold [18] higher COVID-19-related mortality in neurological patients, evaluated by a multivariate approach, while other studies reported, in univariate analyses only, a significant association between mortality and neurological diseases [23] or cerebrovascular and neurodegenerative disorders [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies investigating specific neurological diseases, reported that dementia [4,6,10], stroke [4,[11][12][13], and Parkinson's disease (PD) [14,15] may be associated with higher mortality. Other studies, applying a generic definition of "neurological disorders", reported higher mortality in patients affected by neurological diseases [4,[16][17][18], while a recent systematic review and meta-analysis on the impact of comorbidities on COVID-19 severity, hospitalization, and mortality did not include any neurological disease in the analysis due to the lack of data available [19]. Against this background, no previous studies have comprehensively analyzed the impact of different types of neurological diseases on the outcome of COVID-19 using a cohort design with matched patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that older age 1 , 2 and comorbidities including asthma, chronic obstructive pulmonary disease (COPD), diabetes, and heart and renal disease are associated with severe COVID‐19. 3 , 4 , 5 , 6 , 7 However, association between some neurological condition such as Parkinson's disease, demyelinating disorders, and epilepsy have not been examined extensively. Furthermore, non‐White racial and ethnic persons are reportedly disproportionally affected by COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…Jacobson et al ( 2020 ) examined and found that there have been intense searches in Google to find about stress, insomnia, negativity, and even suicidal thoughts. In their qualitative research, Williams et al ( 2020 ) mentioned that participants reported their helplessness in adjusting longer-term and experienced issues of non-adherence in seeing or hearing others at the beginning of the social distancing measures. The present study also demonstrates the psychological state of the participants after suffering financial losses, facing perpetual work-life challenges, and trying to comprehend the fundamental meaning of existence after the pandemic outbreak.…”
Section: Discussionmentioning
confidence: 99%